2010
DOI: 10.1002/chem.201000174
|View full text |Cite
|
Sign up to set email alerts
|

Carbodicarbenes and Related Divalent Carbon(0) Compounds

Abstract: Quantum-chemical calculations using DFT and ab initio methods have been carried out for fourteen divalent carbon(0) compounds (carbones), in which the bonding situation at the two-coordinate carbon atom can be described in terms of donor-acceptor interactions L-->C<--L. The charge- and energy-decomposition analysis of the electronic structure of compounds 1-10 reveals divalent carbon(0) character in different degrees for all molecules. Carbone-type bonding L-->C<--L is particularly strong for the carbodicarben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
89
1
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 87 publications
(258 reference statements)
8
89
1
10
Order By: Relevance
“…L to a wider range of donor ligands beyond L = PPh 3 . [10][11][12][13][14] A new class of carbones termed carbodicarbenes CA C H T U N G T R E N N U N G (NHC) 2 (NHC=N-heterocyclic carbene) (2 C, Scheme 1), which features unusual carbon!carbon donor-acceptor bonds between a naked carbon(0) atom in the 1 D state as an acceptor and N-heterocyclic carbene ligands as donors, was predicted to be stable enough to become isolated. [10] Several examples of carbodicarbenes with NHC and other carbene ligands have in the meantime become synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…L to a wider range of donor ligands beyond L = PPh 3 . [10][11][12][13][14] A new class of carbones termed carbodicarbenes CA C H T U N G T R E N N U N G (NHC) 2 (NHC=N-heterocyclic carbene) (2 C, Scheme 1), which features unusual carbon!carbon donor-acceptor bonds between a naked carbon(0) atom in the 1 D state as an acceptor and N-heterocyclic carbene ligands as donors, was predicted to be stable enough to become isolated. [10] Several examples of carbodicarbenes with NHC and other carbene ligands have in the meantime become synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] In each case, both lone pairs of electrons on carbon were predicted and confirmed to be chemically accessible. [11][12][13] Phosphine-stabilized "C 3 " has also been reported, but not structurally verified. [14] NHC-stabilized "allotropes" of "E 2 " have been reported for Si/Ge from Group 14, and P/As from Group 15.…”
mentioning
confidence: 99%
“…Proton affinity (PA) has been used to measure the potential for atom centers to act as ligands for related compounds, such as 1 and 2. [11,13,24] The first (PA1) and second (PA2) proton affinities for 5 and 6 (Table 1) are very high. PA1 ranges from 1163 kJ mol À1 for 5 Me to 1256 kJ mol À1 for 6 Ph.…”
mentioning
confidence: 99%
“…[4] New carbodicarbenes and related compounds have recently been calculated in a theoretical study [5] that showed that other divalent carbon(0) compounds had already been previously synthesized, but the donor-acceptor bonds had not been identified. [6] It was suggested that, in the light of recent theoretical and experimental findings, there should be a rethinking regarding the bonding of carbon.…”
Section: Susanne Klein and Gernot Frenking*mentioning
confidence: 99%